A Systematic Review of the Relationship between Child Sexual Abuse and Substance Use Issues. Issue 3 (3rd April 2021) - Fletcher, Kara
ABSTRACT: Child sexual abuse (CSA) and substance use issues later in life have been well documented in the literature. This systematic review from 2009 to 2019 provides an update on what is known about the relationship between CSA and substance use. While the review confirms a clear relationship between CSA and substance use, it also highlights some potential gaps in our current practices, including an acknowledgment of the other risk factors associated with CSA and substance use issues, as well as the need to develop treatment that specifically screens for and addresses CSA in the context of substance use.